Metodologia para a determinação de cátions inorgânicos em formulações minerais e fitoquímicas por eletroforese capilar com detecção condutométrica - Raabe, Alice (2010)
The selective determination of inorganic cations, like alkaline, earth-alkaline, of transition and the ammonium ion (NH4 +) is considered as a difficult practice, because generally, these ions show very close apparent mobilities, by the similarities in their sizes (hydrated ionic rays) and same charges, in some cases it may make the separation not viable. This work describes the simultaneous determination of 14 analytes: ammonium (NH4 +), potassium (K+), calcium (Ca2+), sodium (Na+), magnesium (Mg2+), manganese (Mn2+), thallium (Tl+), chrome (Cr3+), lead (Pb2+), cadmium (Cd2+), zinc (Zn2+), copper (Cu2+), cobalt (Co2+) and nickel (Ni2+). The mechanism of separation used was the capillary zone electrophoresis (CZE, capillary zone electrophoresis) with capacitively coupled contactless conductivity detection (C4D, capacitively coupled contactless conductivity detection) CZE-C4D. The experimental conditions optimized to the determination of cations were: working electrolyte 30 mmol L-1 MES/His, containing 1.5 mmol L-1 18-crown-6 ether, in pH 6; followed by a second stage containing 1 mmol L-1 citric acid in its composition to the selective determination of ions K+ and Tl+. Even other operational parameters with the separation potential of -10 kV, the work temperature of 25 ±1°C, hydrodynamic injection by the samples gravity (20 cm versus 60 s), and the detector C4D operating with the frequency of 600 kHz and varying the amplitude in 2 Vpp (peak to peak). The developed methodology was evaluated for the 14 analytes, where the method was shown adequate to the determination of inorganic cations studied, showing wide linear work rates of 5.18 to 2,217.06 Umol L-1 and of 19.00 to 1,538.46 Umol L-1 for ions NH4 + and Cr3+, respectively; also showing limits of detection (LD) and of quantification (LQ) in the order of Umol L-1 for all analytes. The study also involved the analysis of the alkaloids in real samples and in distinct molds, like phytotherapyc formulations and formulations of mineral fertilizers.